Pengaruh Kombinasi Model Pembelajaran Kooperatif Dan Motivasi Berprestasi Terhadap Hasil Belajar Matematika (Studi Eksperimen Pada siswa Kelas VIII SMP Negeri 10 Kendari) - La Masi; Jumiati Hamade (Jurnal Pendidikan Matematika, 2016)
The experimental design used in this research was factorial 2 x 2 design with the total sample of 60 students in 8th Grade SMP Negeri 10 Kendari.  The purpose of this research were (1) to study about the effect students’ achievement motivation on mathematics’ learning outcomes (2) to study about the combined effect of cooperative learning model (TSTS-STAD) and achievement motivation as a level which consists of the upper group and the bottom group. (1) The results of descriptive showed that empirical mean value of the results in learning mathematics in each cell relatively support the hypothesis, (2) the results inferential analysis  showed that achievement motivation has a significant positive impact on learning outcomes of mathematics with a contribution of 0.530 unit which means that any change in one unit of achievement motivation would improve mathematics learning outcomes of 0.530 units with a contribution of 64.3% and 35.7% is determined by other factors in the population. The results of inferential analysis through ANOVA 2 factors non-hierarchy and hierarchy based on statistical F test at 0.05 significan levels receive all the hypotheses H0 means the average mathematics learning outcomes in each cell has a relatively significan.